C-reactive protein in early-onset neonatal sepsis – a cutoff point for CRP value as a predictor of early-onset neonatal sepsis in term and late preterm infants early after birth?. (2nd December 2022) - Yochpaz, Sivan; Friedman, Nati; Zirkin, Semyon; Blumovich, Amit; Mandel, Dror; Marom, Ronella
Abstract: Objective: To identify whether the first plasma C-reactive protein values taken 6–8 h postpartum are predictive of the clinical early-onset neonatal sepsis (cEONS). Study design: We retrospectively analyzed C-reactive protein (CRP) values of 400 neonates, including 28 with cEONS, who underwent plasma CRP measurements as part of sepsis work-up. To determine whether the first CRP measurement is predictive of cEONS, logistic regression was used with CRP as an independent variable and cEONS (yes/no) as a dependent variable. Result: A moderate predictive ability of the first CRP measurement (odds ratio 1.4, CI: [1.13, 1.76], p =.003) was revealed, at a 5.3 mg/L threshold. However, it resulted in poor sensitivity of 50%, and a false positive rate of 30%. Increasing the sensitivity to 75% or 90% lead to increased false-positive rates of 55% and 75%, respectively. Conclusions: Our findings suggest that the first CRP value taken in neonates is a weak predictor of cEONS.